Non-prosecution agreement and the paradigm of prevention in the fight against corruption and economic macrocriminality in Brazil: new alternatives to the traditional punitive model - Soraia da Rosa Mendes; Augusto César Borges Souza (Revista Brasileira de Direito Processual Penal)
This article intends to analyze the recent legislative changes that have occurred in Brazil, especially the establishment of consensual forms of dispute resolution and their impacts in the fight against corruption and economic macro-criminality. Using the idea of technical prevention as proposed by Winfried Hassemer as a theoretical framework, it is intended to assess whether negotiated criminal justice represents an effective alternative to the dominant punitivist paradigm, with greater ability to reduce impunity and increase crime prevention indexes related to offenses against Public Administration and the economic order. Initially, some criminological aspects of corruption and macroeconomic criminality will be addressed, as well as political-criminal factors, which place the ideal of prevention as the central vector of the contemporary criminal justice system. Then, the insufficiency of the traditional model of Brazilian criminal prosecution, based on litigation, and its inefficiency in dealing with cases related to economic macro-crime and corruption will be analyzed. Finally, the main aspects related to the implementation of new consensual forms of dispute resolution in the criminal field, the political-criminal prognoses in the treatment of corruption and organized crime and their impacts on the performance of prosecution and judicial branch.